2016
DOI: 10.1515/jvetres-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tumour escape from immune surveillance

Abstract: The progressive growth and spread of tumour cells in the form of metastases requires an interaction of healthy host cells, such as endothelial cells, fibroblasts, and other cells of mesenchymal origin with immune cells taking part in innate and adaptive responses within the tumour lesion and entire body. The host cells interact with tumour cells to create a dynamic tumour microenvironment, in which healthy cells can both positively and negatively influence the growth and spread of the tumour. The balance of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Various mechanisms explaining the immune escape have been proposed, including immune editing, targeting regulatory T‐cell function, antigen presentation, modification of immunosuppressive mediators, tolerance and immune deviation, and apoptosis of cytotoxic T cells. While recognizing the complexities of and interactions between these various mechanisms, I shall focus here on the role of the Kyn metabolite precursor Trp in immune escape and, in particular, Trp availability to tumors and its physiological determinants will be identified and means of limiting this availability will be proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms explaining the immune escape have been proposed, including immune editing, targeting regulatory T‐cell function, antigen presentation, modification of immunosuppressive mediators, tolerance and immune deviation, and apoptosis of cytotoxic T cells. While recognizing the complexities of and interactions between these various mechanisms, I shall focus here on the role of the Kyn metabolite precursor Trp in immune escape and, in particular, Trp availability to tumors and its physiological determinants will be identified and means of limiting this availability will be proposed.…”
Section: Introductionmentioning
confidence: 99%
“…However, in breast cancer patients the relationship between PD-L1 expression and prognosis remains unclear. Some studies have shown that positive PD-L1 was associated with significantly poor survival (Lisiecka and Kostro, 2016), but other studies could not confirm these findings ( Park et al, 2016). These discrepancies may be due to different thresholds were used to determine expression positivity and because the studies included populations of different races.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has become very clear that malignant cells must be able to successfully evade immune surveillance to progress and metastasis. Tumor cells use a variety of different pathways to achieve this goal (Lisiecka and Kostro , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, tumor cells can get away from body immune superintendence when changing their biological properties. The functions of immune factors in the incidence, progression, and healing of tumor has provided great interest in immunology of tumor and immunotherapy of cancer (Lisiecka and Kostro, 2016[ 56 ]; Mohme et al, 2017[ 66 ]). Several therapeutic approaches have designed to attack tumors directly.…”
Section: Introductionmentioning
confidence: 99%